EARTH'S CREATION STIMULUS: CREATION OF GRAPHIC ARTS WITH USED PLYWOOD MEDIA - Adi, Sigit Purnomo; Sukerta, Pande Made; Marianto, M. Dwi; Hadi, Sri (ISI Press Institut Seni Indonesia Surakarta, 2021)
Natural phenomena, especially climate change, are increasingly worrying lately. Graphic art can be used to express concern for the environment in response to climate change. The creation of this graphic art work uses the concept of the earth's creation stimulus. The creative methods used include: experimentation, contemplation, and formation. Abstract Expressionism was chosen as the style of personal expression in the creation of this work. The creative technique used is high printing technique with used plywood media. The results of the creation process show that the visualization of the concept of the earth's creative stimulus produces the forms of circles and lines. These forms are the main motif in the creation of graphic art with the stimulation of this earth's creativity